Эффективное использование природных ресурсов как важный фактор в международном сотрудничестве - Хакимов, Н.Х. (Культура народов Причерноморья, 2013)
В статье рассматриваются международные аспекты эффективного использования природных ресурсов Центральной Азии на примере Республики Узбекистан. Автор исследовал возможности экологического туризма как важного фактора развития отрасли и национальной экономики в целом. У статті розглядаються міжнародні аспекти ефективного використання природних ресурсів Центральної Азії на прикладі Республіки Узбекистан. Автор досліджував можливості екологічного туризму як важливого чинника розвитку галузі та національної економіки в цілому. The article deals with the international aspects of the efficient use of natural resources of Central Asia especially in the Republic of Uzbekistan. As a UN member, Uzbekistan acceded to most Conventions on Environment and Sustainable Development, regarding them as effective international legal instruments and mechanisms. International cooperation is carried out in the framework of international agreements, which allow avoiding duplication of efforts. This is achieved through the implementation of joint programs, particularly in the areas of research, training, systematic observation and information sharing, coordination, and identification of measures that can be simultaneous. The five Central Asian countries signed two declarations on environmental issues. The local authorities perform a number of bilateral and multilateral agreements, such as joint actions of recultivating the sites with mining wastes that have transboundary impact. Currently, Uzbekistan is involved in the development of a joint initiative of the countries of Central Asia on land resources management aimed at creating and implementing national programs of preventing land degradation by promoting the principles of sustainable resources management.